Some Terminally Alkenyl-substituted Porphyrins: Synthesis and Attempts of Heck Reaction Leading to Porphyrin–Azulene Dyads - Ostrowski, Stanisław; Grzyb, Sebastian; Godlewski, Bartosz (Current Organic Chemistry, 2024)
The synthesis of meso-tetraphenylporphyrin derivatives, double functionalized in one of the phenyl rings (with a nitro group and carbon substituents), is described. 5-(4- Nitroaryl)-10,15,20-triarylporphyrinates react, in the presence of a base (t-BuOK), with carbanions containing a leaving group at the carbanionic center to give products of substitution of hydrogen at ortho-position to the nitro group via vicarious nucleophilic substitution scheme. Their alkylation with allyl bromide or 4-bromobut-1-en (t-BuOK/DMF, at 0-5°C) leads to porphyrins bearing side alkyl chain with a terminal double bond in yields of up to 82%. The above-mentioned double-substituted intermediates are very convenient substrates for Heck cross-coupling reaction. In this study, the synthesis of porphyrin–azulene dyads is reported. In some cases, the formation of highly conjugated systems is observed, with moderate yield. Their structures are interesting from both the porphyrin and azulene point of view.
Keywords: palladium